2022
DOI: 10.1002/jbt.23063
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of resveratrol on diazinon‐induced oxidative stress and glucose hemostasis disorder in rats' liver

Abstract: This study was intended to assess the possible protective effect of resveratrol (Res) against oxidative stress and glucose hemostasis disorder in rats exposed to diazinon (DZN) for 4 weeks. Totally 25 Sprague-Dawley rats were divided randomly into five groups: Control (orally received corn oil), DZN group (orally received 70 mg/kg/day), and Res groups (received DZN 70 mg/kg/day plus Res doses of 5, 10, and 20 mg/kg bodyweight/-day), respectively. DZN significantly inhibited serum acetylcholinesterase enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…It can maintain the balance between cell proliferation and apoptosis, and reduce nuclear chromatin clumping in ovarian granulosa cells [245]. Resveratrol (Res) is a natural plant-derived phenol with excellent antioxidant activity [246]. Res has been found to attenuate the damage caused by cyclophosphamide on ovarian function, including reducing OS damage, inhibiting apoptosis and promoting ovarian stem cell repair [18].…”
Section: Antioxidant Monomersmentioning
confidence: 99%
“…It can maintain the balance between cell proliferation and apoptosis, and reduce nuclear chromatin clumping in ovarian granulosa cells [245]. Resveratrol (Res) is a natural plant-derived phenol with excellent antioxidant activity [246]. Res has been found to attenuate the damage caused by cyclophosphamide on ovarian function, including reducing OS damage, inhibiting apoptosis and promoting ovarian stem cell repair [18].…”
Section: Antioxidant Monomersmentioning
confidence: 99%
“…As noted throughout this manuscript, oxidative stress has been proposed to play a pathological role in DZN poisoning and the liver is an important target organ of this pesticide. In this way, natural antioxidants compounds from different sources have been studied as protective agents of the DZN-induced liver toxicity [42] , [46] , [5] , [11] . The present study demonstrated that THC prevented HepG2 cell death induced by DZN.…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol treatment can reverse the experimental induced oxidative stress condition and upregulate SIRT1 expression. 111 Taguchi et al reported that resveratrol ameliorates local inflammation in endometriosis by suppressing TNF-α-induced IL-8 release in a dose-dependent manner via the SIRT1 pathway. 112 …”
Section: Molecular Mechanisms Of Resveratrol Against Endometriosismentioning
confidence: 99%
“… 127 In diazinon (DZN)-induced oxidative stress rat models, Mehri et a reported that DZN inhibits serum acetylcholinesterase (AChE) as well as serum and liver CAT, GSH-Px, and total antioxidant abilities, and they also demonstrated that resveratrol reverses the oxidative stress conditions, improves the activity of antioxidant enzymes, and lower MDA level in the serum and liver. 111 …”
Section: Molecular Mechanisms Of Resveratrol Against Endometriosismentioning
confidence: 99%